The Reality of Using Educational Technology in Teaching English Perspectives of Female English Teachers in Primary and Middle Schools in Sabya City - Almalki, Fatimah Jaber Frhan (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the reality of education technology availability to teach the English language from the perspectives of female English teachers in primary and middle schools in Sabya City and the reality of applying this technology in teaching. The study also aimed to identify the challenges faced by female English teachers in implementing education technology in their profession in Sabya and define the significance of statistical differences at the level of (α≤ 0.05) for female English teachers significance attributed to the variables of years of service (≤ 5 years and > 5 years in service) and different training sessions (≤ 3 and > 3 training sessions). The study's population consisted of female English teachers in primary and middle schools in the second semester of the academic year 1440-1441 H; while randomly selecting (110) female teachers from Sabya City. The researcher followed the Descriptive Analytical method and designed a questionnaire for data collection. The study's results showed that educational technology availability in teaching English in the primary and middle schools in the city was below the required level. The results also indicated that the implementation of educational technology by female English teachers at primary and middle schools did not reach the required level. furthermore, the study indicated that the challenges faced by the teachers at the primary and middle schools in implementing educational technology in Sabya were significant; the most prominent of which was the educational supervisor's failure to follow-up on the use of modern educational technology in education, the lack of adequate and appropriate computerized pedagogical programs for the English language curriculum, and limited school budget; because no budget was allocated for the purchase of educational technology. The study found differences between the averages of the sample's responses regarding the reality of implementing educational technology in teaching English from the perspectives of female English teachers in primary and middle schools in Sabya attributable to years of service (≤ 5 years and > 5 years in service) at a significant level of; as these differences were in favor of (> 5 years in service) category. Moreover, there were differences between the averages of the sample's responses regarding the reality of implementing educational technology in teaching English from the perspectives of female English teachers in primary and middle schools in Sabya attributable to the difference in training sessions (≤ 3 and > 3 training sessions) at a significance level of; as these differences were in favor of (> 3 training sessions) category. The study concluded with several recommendations, the most important of which were: The necessity of using educational technology in teaching English in its various subjects on the educational process and the necessity of training female teachers to use educational technology through conducting training sessions in the field of teaching for development.
Keywords: Educational Technology; primary and middle schools; Teaching English